2016
DOI: 10.1007/s11701-016-0587-7
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of robot-assisted pedicle screw placement for adolescent idiopathic scoliosis in the pediatric population

Abstract: This is a retrospective review of pedicle screw placement in adolescent idiopathic scoliosis (AIS) patients under 18 years of age who underwent robot-assisted corrective surgery. Our primary objective was to characterize the accuracy of pedicle screw placement with evaluation by computed tomography (CT) after robot-assisted surgery in AIS patients. Screw malposition is the most frequent complication of pedicle screw placement and is more frequent in AIS. Given the potential for serious complications, the need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 16 publications
1
70
0
Order By: Relevance
“…Macke et al also found a decrease in misplacements when comparing the first and last third of their cohort (9.6% vs 7.4%). 22 However, Ringel et al stated that accuracy did not improve over the course of their study, although no specific data were provided.…”
Section: Learning Curvementioning
confidence: 97%
See 3 more Smart Citations
“…Macke et al also found a decrease in misplacements when comparing the first and last third of their cohort (9.6% vs 7.4%). 22 However, Ringel et al stated that accuracy did not improve over the course of their study, although no specific data were provided.…”
Section: Learning Curvementioning
confidence: 97%
“…2,5,6,9,[11][12][13][14][15]17,21,22,24,25,[27][28][29][30][31][35][36][37] Twenty-one of these studies used variations of the robot developed by Mazor, whereas 1 study evaluated the ROSA robot. Twenty-one studies evaluated pedicle screw accuracy, whereas Dreval et al evaluated both pedicle screws and guided oblique lumbar interbody fusion (GO-LIF) screws, 6 and Bederman et al evaluated the accuracy of S2-alar-iliac screw placement.…”
Section: Accuracy Of Spinal Instrumentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, robot-assisted spinal operation involves the preoperative or intraoperative acquisition of images and image-guided surgery after registration and calibration [9,10].…”
Section: Introductionmentioning
confidence: 99%